THE INFLLUENCE OF TEMPERATURE ON THE CORROSION BEHAVIOUR OF GLASS FIBRE REINFORCED POLYMER STRENGTHENED STEEL - Abdul Halim, Muhammad Hafiz (IRC, 2021)
The project is to evaluate the effectiveness and method on enhancing the properties of Carbon Steel by applying heat treatment for the production of oxide layer on the material’s surface and by attaching the Carbon Steel with glass fibre reinforced polymer (GFRP) to fabricate a type of Fibre Metal Laminates (FML).